A new species of Notaepytus Skelley, 2009 (Coleoptera: Erotylidae: Tritomini) from Dominican amber - Keller, Oliver; Skelley, Paul E. (Zootaxa, 2019)
Notaepytus quisqueya sp. nov. (Erotylidae: Erotylinae: Tritomini), is described here from Dominican amber and is the second amber fossil description for the family from the West Indies (Hispaniola). An emended key and a checklist to all known species of Notaepytus are presented.